Gambaran Pengetahuan Keluarga Dengan Diabetes Melitus Tentang Pencegahan Komplikasi Diabetes Melitus Di Wilayah Kerja Puskesmas Sentolo 2 - Agustina Rahmawati; Wahyu Ratna; Rosa Delima Ekwantini (Poltekkes Kemenkes Yogyakarta, 2017)
Diabetes mellitus can causes various complications that has to prevent early. Prevention of the complications can be conducted by a good management. Family has a function as a caregiver. A good caregiver needs a sufficient knowledge. This research was to determine the description of family’s knowledge about complication prevention of Diabetes Mellitus in coverage of Sentolo 2 Local Goverment Clinic. This research conducts descriptive research with survey design. Subject of this research are family that have member with Diabetes Mellitus disease. Quota sampling was employed for 85 respondents. The kind of instrument that used is a questionnaire. The result of this research shows that 51 respondents (60%) are women, 24 respondents (28,24%) are 46-55 years old, 43 respondents (50,59) are graduated from Senior High School, 21 respondents (24,71%) work as entrepreneur and 70 respondents (82,35%) have already got information about diabetes mellitus. Respondents’s knowledge about dietary with good criteria are 60 respondents (70,59)%, knowledge about physical activities with sufficient criteria are 55 respondents (64,71%), knowledge of blood sugar control with good criteria are 63 respondents (74,12%), knowledge of pharmacology therapy with good criteria are 43 respondents (50,59%), and knowledge about health examination with sufficient criteria are 37 respondents (43,53%). Family’s knowledge about prevention of diabetes melitus complication in coverage of Sentolo 2 Local Goverment Clinic have a sufficient criteria.